Curcumin Attenuates Hippuric Acid-Induced Eryptosis by Enhancing Antioxidant Enzyme Activity - Butt, Namra; Nasir, Sadia; Ahmad, Urwah; Haider, Masooma; Haider, Imrana; Murtaza, Alina; Javaid, Zara; Hassan, Muhammad Najamul; Jilani, Kashif (Indus Journal of Bioscience Research, 2025)
Background: Eryptosis, the programmed death of erythrocytes, is exacerbated under pathological conditions such as chronic kidney disease (CKD), largely due to the accumulation of uremic toxins like hippuric acid. These toxins promote oxidative stress and disrupt erythrocyte membrane integrity, leading to hemolysis and anemia. Curcumin, a polyphenolic compound derived from Curcuma longa, is well known for its potent antioxidant and cyto-protective properties, yet its protective role against uremic toxin-induced eryptosis remains underexplored. Objective: This study aimed to investigate the protective effects of curcumin against hippuric acid-induced eryptosis in human erythrocytes and to explore the involvement of oxidative stress and calcium influx in the onset of eryptosis. Methods: Human erythrocytes were treated with different concentrations of hippuric acid (300 -430 μM) and curcumin (5-15 μM) for 48 hours. The hemolysis % was determined to assess the cytotoxic effect of hippuric acid. The oxidative potential of hippuric acid and antioxidant potential of curcumin was determining by assessing the activities of antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase. Morphological changes were assessed via mean corpuscular volume (MCV). Amlodipine was used to confirm the role of calcium in eryptosis. Results: Hippuric acid significantly increased hemolysis %, reduced MCV, and suppressed activity of antioxidant enzymes (SOD, GPx, and CAT). Curcumin co-treatment markedly attenuated hemolysis %, restored MCV, and significantly upregulated antioxidant enzyme activity. Amlodipine pretreatment effectively blocked calcium channels thus mitigated the effect of hippuric acid. Conclusion: Curcumin protects erythrocytes from hippuric acid-induced eryptosis by restoring antioxidant defenses and providing cyto-protective properties. These findings reveal the protective mechanisms of curcumin and suggest its potential utility as a natural therapeutic agent to mitigate erythrocyte damage in CKD and related oxidative stress conditions.